2014
DOI: 10.1590/1414-462x201400030006
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation and psychometric properties of social cognitive scales related to adolescent dietary behaviors

Abstract: Establishing valid and reliable methods for assessing social cognitive measures of dietary behaviors support the design and delivery of more effective interventions. The aims of this study were to culturally adapt social cognitive measures related to adolescent dietary behaviors and evaluate the reliability and factorial validity of these measures in Brazilian adolescents. The instrument was culturally adapted from an Australian questionnaire based on the Banduras' Social Cognitive Theory, and it included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…The test-retest reliability, assessed on the 26 subjects, 5 weeks after the first evaluation, highlighted an ICC value of 0.65 that is considered an adequate level of repeatability. 46 …”
Section: Resultsmentioning
confidence: 99%
“…The test-retest reliability, assessed on the 26 subjects, 5 weeks after the first evaluation, highlighted an ICC value of 0.65 that is considered an adequate level of repeatability. 46 …”
Section: Resultsmentioning
confidence: 99%
“…A review suggest that interventions aimed at changing health behaviors in adolescents should target the key constructs of the theories [ 84 ]. For example, the core construct of the SCT is self-efficacy, which is the individual confidence in personal ability to acquire a certain health behavior [ 85 ]. Research criterion and findings with adolescents suggested that these constructs are important and reliable mechanisms of dietary and PA behaviors that can be changed when using extant intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, "self-efficacy", the key construct of the social cognitive theory (SCT) is similar to "perceived behavioral control" (PBC) of the theory of planned behavior (TPB). Moreover, attitudes in the TPB are comparable to the expectations of the SCT, which is related to physical and cognitive beliefs about healthy eating (e.g., healthy eating can help weight control) [53].…”
Section: Discussionmentioning
confidence: 81%